2014
DOI: 10.1038/srep06226
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylases inhibition by SAHA/Vorinostat normalizes the glioma microenvironment via xCT equilibration

Abstract: Malignant gliomas are characterized by neurodegenerative actions leading to the destruction of surrounding brain parenchyma. The disturbance in glutamate homeostasis caused by increased expression of the glutamate transporter xCT plays a key role in glioma progression. We demonstrate that the HDAC-inhibitor SAHA specifically inhibits the xCT-transporter expression. Thereby, tumor cell stress is engendered, marked by increase in ROS. Moreover, SAHA dependent xCT-reduction correlates with the inhibition of ATF4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Altogether, these data strengthen the therapeutic potential of xCT targeting strategies that would be beneficial to reduce or switch off glutamate metabolism in glioblastoma cells and keep TAMs in a neuroprotective state needed to restore homeostasis after tumor elimination. 36,37 Collectively, these data suggest a putative neuroprotective role of TAMs by taking up excess extracellular glutamate by increasing expressions of glutamate transporters and glutamine synthetase. This response is not completely mimicked by MDMs exposed to tumor cells, further emphasizing the difference in origin between these bone-marrow derived myeloid cells and the yolk sac-derived microglia.…”
Section: Discussionmentioning
confidence: 84%
“…Altogether, these data strengthen the therapeutic potential of xCT targeting strategies that would be beneficial to reduce or switch off glutamate metabolism in glioblastoma cells and keep TAMs in a neuroprotective state needed to restore homeostasis after tumor elimination. 36,37 Collectively, these data suggest a putative neuroprotective role of TAMs by taking up excess extracellular glutamate by increasing expressions of glutamate transporters and glutamine synthetase. This response is not completely mimicked by MDMs exposed to tumor cells, further emphasizing the difference in origin between these bone-marrow derived myeloid cells and the yolk sac-derived microglia.…”
Section: Discussionmentioning
confidence: 84%
“…In this regard, it has been shown that SAHA treatment in glioblastoma cells induces downregulation of xCT, a glutamate-cysteine transporter that controls the intracellular level of reduced glutathione (67). Accordingly, in triple negative breast cancer cells, it has been shown that xCT knockout increases doxorubicin efficacy (60).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, multiple end points for HDAC-inhibitor activity have been reported, including gene expression, cell-cycle arrest, cell differentiation, antiangiogenesis, cell death, and autophagy. 81 In addition, HDAC inhibitors have been reported to generate ROS and modulate redox levels in cells, [82][83][84][85][86][87] resulting in DNA damage and activation of the DDR. 88,89 Others have shown that key DNA-repair molecules including Ku70/Ku80, DNA-PK, RAD50, RAD51, BRCA1/2, and MRE11 are downregulated by vorinostat and other HDAC inhibitors in combination with radiotherapy, leading to RIF persistence.…”
Section: Chromatin Structure and Targetingmentioning
confidence: 99%
“…162 Interestingly, the HDAC inhibitor vorinostat has been shown to normalize xCTcontaining transporter levels in gliomas with an accompanying increase in ROS levels. 86 The cysteine transport system maintains intracellular cysteine and glutathione pools in many cells to counter oxidative stress. This system is under control of nuclear factor-erythroid 2 p45-related factor 2 (Nrf2), which provides a potential link for CSC radioresistance through expression of free-radical scavengers.…”
Section: Cancer Stem Cells and Radiotherapymentioning
confidence: 99%